2021
DOI: 10.1021/jacs.1c01573
|View full text |Cite
|
Sign up to set email alerts
|

Anion Exchange of Ruddlesden–Popper Lead Halide Perovskites Produces Stable Lateral Heterostructures

Abstract: Heterostructures of three-dimensional (3D) halide perovskites are unstable because of facile anion interdiffusion at halide interfaces. Two-dimensional (2D) Ruddlesden–Popper halide perovskites (RPPs) show suppressed and anisotropic ion diffusion that could enable stable RPP heterostructures, yet the direct and general growth of lateral RPP heterostructures remains challenging. Here, we show that halide miscibility in RPPs decreases with perovskite layer thickness (n), enabling the formation of sharp halide la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…The broad peak can be attributed to the distribution of a series of quantum well domains. [ 42 ] The ground state bleaching (GSB) of the two perovskite films has a redshift with the increase of time, which is due to the energy transfer of the wide bandgap component to the narrow bandgap component. [ 43 ] Furthermore, the two perovskites prepared with TPPO antisolvent treatment demonstrate more redshift absorption, indicating that TPPO can promote to form larger n‐value quasi‐2D perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…The broad peak can be attributed to the distribution of a series of quantum well domains. [ 42 ] The ground state bleaching (GSB) of the two perovskite films has a redshift with the increase of time, which is due to the energy transfer of the wide bandgap component to the narrow bandgap component. [ 43 ] Furthermore, the two perovskites prepared with TPPO antisolvent treatment demonstrate more redshift absorption, indicating that TPPO can promote to form larger n‐value quasi‐2D perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…[41] The greater stability of perovskite solar cells have been achieved with 3D/2D hybrid devices. [16,[41][42][43] In the present experiments, we irradiated 2D mixed halide (Br:I = 50:50) perovskites films of different layers (n) with visible light (1 Sun, 100 mW cm −2 ) for 30 min. Absorption spectra of three perovskite films (n = ∞, 6, and 1) recorded during photoirradiation are shown in Figure 2A-C.…”
Section: Effect Of Dimensionality On Halide Segregation and Dark Recoverymentioning
confidence: 99%
“…We have previously shown that reducing the layer number ( n in R 2 A n –1 Pb n X 3 n +1 ) in PEA-based 2D perovskites increases the activation energy for halide mobility . However, despite the suppression of ion migration, even purely n = 1 2D perovskites can be susceptible to the highly mobile nature of the halide ions. In 3D perovskites, alloying cations like cesium into methylammonium lead halide perovskites stiffens the lattice and suppresses halide segregation. , A similar effect may be happening here, as PEA cations are known to stiffen the perovskite lattice due to π-hydrogen bonding in the aromatic ring. …”
mentioning
confidence: 97%